A case of mistaken identity: CD11c‐eYFP+ cells in the normal mouse brain parenchyma and neural retina display the phenotype of microglia, not dendritic cells. Issue 8 (18th May 2016) - Dando, Samantha J.; Naranjo Golborne, Cecilia; Chinnery, Holly R.; Ruitenberg, Marc J.; McMenamin, Paul G.
Abstract : Under steady‐state conditions the central nervous system (CNS) is traditionally thought to be devoid of antigen presenting cells; however, putative dendritic cells (DCs) expressing enhanced yellow fluorescent protein (eYFP) are present in the retina and brain parenchyma of CD11c‐eYFP mice. We previously showed that these mice carry the Crb1 rd8 mutation, which causes retinal dystrophic lesions; therefore we hypothesized that the presence of CD11c‐eYFP + cells within the CNS may be due to pathology associated with the Crb1 rd8 mutation. We generated CD11c‐eYFP Crb1 wt/wt mice and compared the distribution and immunophenotype of CD11c‐eYFP + cells in CD11c‐eYFP mice with and without the Crb1 rd8 mutation. The number and distribution of CD11c‐eYFP + cells in the CNS was similar between CD11c‐eYFP Crb1 wt/wt and CD11c‐eYFP Crb1 rd8/rd8 mice. CD11c‐eYFP + cells were distributed throughout the inner retina, and clustered in brain regions that receive input from the external environment or lack a blood‐brain barrier. CD11c‐eYFP + cells within the retina and cerebral cortex of CD11c‐eYFP Crb1 wt/wt mice expressed CD11b, F4/80, CD115 and Iba‐1, but not DC or antigen presentation markers, whereas CD11c‐eYFP + cells within the choroid plexus and pia mater expressed CD11c, I‐A/I‐E, CD80, CD86, CD103, DEC205, CD8α and CD135. The immunophenotype of CD11c‐eYFP + cells and microglia within the CNS was similar between CD11c‐eYFP Crb1 wt/wt and CD11c‐eYFP Crb1 rd8/rd8 mice; however, CD11c and I‐A/I‐E expression was significantly increased in CD11c‐eYFP Crb1 rd8/rd8 mice. This study demonstrates that the overwhelming majority of CNS CD11c‐eYFP + cells do not display the phenotype of DCs or their precursors and are most likely a subpopulation of microglia. GLIA 2016. GLIA 2016;64:1331–1349 Main Points: CD11c‐eYFP + cells in the normal mouse CNS do not phenotypically resemble dendritic cells or their immature precursors CD11c‐eYFP + cells are present in the neural retina and brain parenchyma of mice with and without the Crb1 rd8 mutation CD11c‐eYFP + cells are a subpopulation of microglia